PENINGKATAN HASIL BELAJAR LOMPAT JAUH GAYA HANG STYLE DENGAN MEDIA BOLA GANTUNG SISWA KELAS VII.1 SMPN 1 GUNUNG TOAR KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Armaini Armaini (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the learning of long jump students of class VII.1 SMPN 1 Gunung ToarKecamatan Gunung Toar Kecamatan Kuantan Singingi is still low. This study aims to improve students' longjump learning outcomes. From the data analysis, there is an increase of both teacher activity, student activity,and student learning result, that is teacher activity at meeting 1 cycle I the percentage is 62,5% (less) and atmeeting 2 increased to 72,5% (good). In the second cycle of meeting 3 increased again to 85% (very good) andat meeting 4 increased to 90% (very good). Judging from the student activity also increased from the 1st cyclemeeting I was 60% (enough) and at the 2nd meeting increased to 75% (good). In the second cycle of meeting 3 itincreased to 87,5% (very good) and at 4th meeting to 92.5% (very good). Judging from student learningoutcomes, the average base score of 70 increased to 80 in the first cycle of increase 10 points later on the secondcycle increased to 95 on the second cycle of major increase of 15 points. From the data analysis there is anincrease both from teacher activity, student activity, and student learning outcomes. It can be concluded that thesuccess of hanging media can improve the learning result of long jump style style hanging class VII.1 SMPN 1Gunung Toar Kecamatan Gunung Toar Kecamatan Kuantan Singingi.